High-definition electrocardiography, heart rate variability and QT interval assessment in coronary heart disease diagnostics during professional medical examination of railroad workers - A. E. Radzevich; V. V. Popov; M. Yu. Knyazeva (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To investigate the potential of high-definition electrocardiography (HD-ECG), heart rate variability (HRV) and QT interval assessment in diagnosing «silent» myocardial ischemia (SMI) during professional expertise of railroad locomotive drivers. Material and methods. Thirty-eight relatively healthy, but with coronary heart disease (CHD) risk factors, railway locomotive drivers were examined (mean age 45.5±7 years). Bicycle stress test, 24-hour ECG monitoring, echocardiography (EchoCG), myocardial scintigraphy (if necessary), ECG, HD-ECG, and HRV assessment were performed. Results. During the study, new CHD cases were diagnosed in 15 railroad locomotive drivers. 24-hour ECG monitoring was the most effective method for SMI diagnostics. SMI episodes were registered at 24-hour ECG monitoring in 73% of all cases. In SMI patients, SAQRS and QTc-max were the most informative parameters. Conclusion. Non-invasive ECG diagnostics methods: HD-ECG, HRV and interval QT assessment could be used, together with bicycle stress test and 24-hour ECG monitoring, during professional expertise of railroad workers.